MENINGKATKAN PARTISIPASI AKTIF MAHASISWA MELALUI LESSON STUDY PADA MATA KULIAH GEOMETRI RUANG - Untarti, Reni; Kusuma, Anggun Badu (Universitas Tanjungpura, 2018)
This research aims to increase the active participation of students through lesson study courses in the geometry of space subject. This type of research is a qualitative descriptive study with the subject is the class A students of the fourth semesterÂ in academic year 2015/2016 who are in the geometry of spaces subject with the number of students are 35. The instruments used are observation sheets of the students' active participation and documentation in the form of photographs and videos. The research procedures based on the stages of the lesson study were 3 cycles in which each cycle consisting of the activity plan, do, and see. This study shows that the results of learning process with the lesson study designed by the model lecturer and the observer can increase the students' active participation, particularly on the subjects of geometry of space. Keywords: active participation, lesson study, geometry of space.